2002
DOI: 10.1002/ps.476
|View full text |Cite
|
Sign up to set email alerts
|

Temporal, environmental and management factors influencing the epidemiological patterns of sea lice (Lepeophtheirus salmonis) infestations on farmed Atlantic salmon (Salmo salar) in Scotland

Abstract: In association with industry, an extensive database has been established on measurements of sea louse counts on farmed Atlantic salmon for the years 1996 to 2000 from 33 Scottish fish farms. These data include extensive counts on the sea louse species, Lepeophtheirus salmonis, at various stages of the life cycle and in particular the chalimus and mobile stages. There has been considerable speculation as to what factors might affect the abundance of sea lice, much of which is based on limited evidence. Our anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
72
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 10 publications
(12 reference statements)
1
72
2
Order By: Relevance
“…Even though the experimental studies have shown a strong effect of temperature on the development times of Lepeophtheirus salmonis, the effect of water temperature has not been very clear in many long-term epidemiological studies at salmon farms (Tully 1989, Revie et al 2002, 2003. This is particularly true for studies from the coast of Scotland (Revie et al 2002(Revie et al , 2003, where high abundances of salmon lice at the chalimus stage are found throughout the winter months (Heuch et al 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though the experimental studies have shown a strong effect of temperature on the development times of Lepeophtheirus salmonis, the effect of water temperature has not been very clear in many long-term epidemiological studies at salmon farms (Tully 1989, Revie et al 2002, 2003. This is particularly true for studies from the coast of Scotland (Revie et al 2002(Revie et al , 2003, where high abundances of salmon lice at the chalimus stage are found throughout the winter months (Heuch et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly true for studies from the coast of Scotland (Revie et al 2002(Revie et al , 2003, where high abundances of salmon lice at the chalimus stage are found throughout the winter months (Heuch et al 2003). In comparison, there is a clear drop in infection rates over the winter months along the coasts of Norway (Heuch et al 2002, Rikardsen 2004 and the North-East Atlantic (Hogans & Trudeau 1989), a pattern which is also seen for wild sea trout (Heuch et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Previous descriptive epidemiological studies (Bron et al 1993, Wadsworth 1998, Revie et al 2002a) have indicated considerable differences in mobile counts of Lepeophtheirus salmonis according to period within the production cycle on Scottish farms. In the present study, 3 mobile cohorts were examined: the average weekly L. salmonis mobile abundance during the second half of the first year of production (referred to as LepsMob_1.2) and the average weekly mobile abundance during the first and second halves of the second year of production (referred to as LepsMob_2.1 and LepsMob_2.2, respectively); and mobile abundance during the first 6 mo of the first production year, when L. salmonis levels are typically negligible.…”
Section: Methodsmentioning
confidence: 98%
“…Data sources relating to freshwater run-off (Edwards & Sharples 1986) and wild fish runs were not available for the sites during the periods in question. Data on disease challenge, seawater salinity and wind speed were incomplete, and as previous analyses had indicated no regional variations (Revie et al 2002a) it was decided not to pursue ambient light levels as a factor. This led to the omission of 5 factors originally identified by the panel as of interest, and left 4 factors which were also those ranked as most important.…”
Section: Justificationmentioning
confidence: 99%
“…Temperature may be the initial explanation, because earlier studies have demonstrated a positive relationship between water temperature and settlement, survival and developmental rate of other parasitic copepods (Conley and Curtis 1993, Hogans 1995, González and Carvajal 2003. However, this connection has been debated by Revie et al (2002) suggesting that water temperature had no evident effect on mean annual abundance of sea lice, Lepeophtheirus salmonis, in farmed Atlantic salmon and could not be a proper explanation for differences in lice levels. Further studies should investigate variability in water salinity, water temperature and other environmental factors due to geographic variations, which may clarify this paradox and explain the variability in sea lice prevalence across sampling years (Zagmutt-Vergara et al 2005, Khan 2012.…”
Section: Discussionmentioning
confidence: 99%